Biofabrication of nerve fibers with mimetic myelin sheath-like structure and aligned fibrous niche. (11th May 2020) - Chen, Suping; Wu, Chengheng; Liu, Amin; Wei, Dan; Xiao, Yun; Guo, Zhenzhen; Chen, Lu; Zhu, Yuda; Sun, Jing; Luo, Hongrong; Fan, Hongsong
Abstract: Nerve tissues contain hierarchically ordered nerve fibers, while each of the nerve fibers has nano-oriented fibrous extracellular matrix and a core–shell structure of tubular myelin sheath with elongated axons encapsulated. Here, we report, for the first time, a ready approach to fabricate biomimetic nerve fibers which are oriented and have a core–shell structure to spatially encapsulate two types of cells, neurons and Schwann cells. A microfluidic system was designed and assembled, which contained a coaxial triple-channel chip and a stretching loading device. Alginate was used first to assist the fabrication, which was washed away afterwards. The orientation of the biomimetic nerve fibers was optimized by the control of the compositions of methacrylate hyaluronan and fibrin, together with the parameters of microfluidic shearing and external stretching. Also, neurons and Schwann cells, which were respectively located in the core and shell of the fibers, displayed advanced biologic functions, including neurogenesis and myelinating maturation. We demonstrate that the neural performance is relatively good, compared to that resulted from individually encapsulated in single-layer microfibers. The present study brings insights to fabricate biomimetic nerve fibers for their potential in neuroscience research and nerve regeneration. Moreover, the present methodology on the fabrication of oriented fibers with different types of cells separately encapsulated should be applicable to biomimetic constructions of various tissues.